Evaluating wide-field-of-view augmented reality with mixed reality simulation - Donghao Ren; Goldschwendt, Tibor; YunSuk Chang; Hollerer, Tobias (Proceedings of the Workshop on Future Trends of Distributed Computing Systems, 2016)
Full-surround augmented reality, with augmentations spanning the entire human field of view and beyond, is an under-explored topic since there is currently no hardware that can support it. As current AR displays only support relatively small fields of view, most AR applications to-date employ relatively small point-based annotations of the physical world. Anticipating a change in AR capabilities, we experiment with wide-field-of-view annotations that link elements far apart in the visual field. We have built a system that uses full-surround virtual reality to simulate augmented reality with different field of views, with and without tracking artifacts. We conducted a study comparing user performance on five different task groups within an information-seeking scenario, comparing two different fields of view and presence and absence of tracking artifacts. A constrained field of view significantly increased task completion time. We found indications for task time effects of tracking artifacts to vary depending on age.